Mycobacterial acyl carrier protein suppresses TFEB activation and upregulates miR-155 to inhibit host defense - Paik, Seungwha; Kim, Kyeong Tae; Kim, In Soo; Kim, Young Jae; Kim, Hyeon Ji; Choi, Seunga; Kim, Hwa-Jung; Jo, Eun-Kyeong (Frontiers in Immunology, 2022)
Mycobacterial acyl carrier protein (AcpM; Rv2244), a key protein involved in Mycobacterium tuberculosis (Mtb) mycolic acid production, has been shown to suppress host cell death during mycobacterial infection. This study reports that mycobacterial AcpM works as an effector to subvert host defense and promote bacterial growth by increasing microRNA (miRNA)-155-5p expression. In murine bone marrow-derived macrophages (BMDMs), AcpM protein prevented transcription factor EB (TFEB) from translocating to the nucleus in BMDMs, which likely inhibited transcriptional activation of several autophagy and lysosomal genes. Although AcpM did not suppress autophagic flux in BMDMs, AcpM reduced Mtb and LAMP1 co-localization indicating that AcpM inhibits phagolysosomal fusion during Mtb infection. Mechanistically, AcpM boosted the Akt-mTOR pathway in BMDMs by upregulating miRNA-155-5p, a SHIP1-targeting miRNA. When miRNA-155-5p expression was inhibited in BMDMs, AcpM-induced increased intracellular survival of Mtb was suppressed. In addition, AcpM overexpression significantly reduced mycobacterial clearance in C3HeB/FeJ mice infected with recombinant M. smegmatis strains. Collectively, our findings point to AcpM as a novel mycobacterial effector to regulate antimicrobial host defense and a potential new therapeutic target for Mtb infection.